The meaning of the legislative definition of concept "Law-enforcement agencies" for the qualify of threat or violence according to employee of law-enforcement agency - Возьний, Володимир Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The problems of concept «Law-enforcement agencies» are considered in the article, positions of research workers are resulted. Criminal and legal description of object and victims of corpus delict is given «Threat orviolence according to the worker of law-enforcement agency".